Pengaruh Profitabilitas, Leverage dan Ukuran Perusahaan Terhadap Penghindaran Pajak Pada Perusahaan Manufaktur Sektor Industri Makanan dan Minuman Tahun 2018 -2022 - Sudirman, Ganefo; M, Mahwiyah (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
This study aims to determine profitability, leverage and company size are able to influence tax avoidance practices. The data used in this study are the annual reports of manufacturing companies in the food and beverage industry sector listed on the Indonesia Stock Exchange in the period 2018-2022. This study uses a quantitative method. This study uses multiple linear regression analysis tools using the analysis tool, namely SPSS IBM 23. The implications of the study are expected to provide a positive contribution to all parties. For companies, companies can be used as a reference or benchmark for tax avoidance practices on the impact of several ratios in financial statements. This study is also expected to be useful for investors and potential investors in seeing opportunities for tax practices or compliance in manufacturing companies in the food and beverage industry sector listed on the IDX. Regulators can also assess and monitor whether there are indications of fraud on the impact of tax avoidance which of course is not in accordance with the tax regulations in force in Indonesia. Based on the hypothesis in this study, profitability affects tax avoidance, leverage affects tax avoidance and company size does not affect tax avoidance.